Synchrotron radiation transmission by two coupled flat microchannel plates: new opportunities to control the focal spot characteristics. (19th January 2022) - Mazuritskiy, M. I.; Lerer, A. M.; Marcelli, A.; Dabagov, S. B.
Abstract : Transmission properties and diffraction patterns generated by synchrotron radiation at the exit of an assembled couple of microchannel plates (MCPs) are inivestigated. A theoretical model to simulate the patterns and properties of the soft X‐ray beam emerging from this couple of MCPs is presented and discussed. Abstract : An improved theoretical model to calculate the focal spot properties of coherent synchrotron radiation (SR) soft X‐ray beams by combining and aligning two microchannel plates (MCPs) is presented. The diffraction patterns of the radiation behind the MCP system are simulated in the framework of the electrodynamical model of the radiation emission from two‐dimensional finite antenna arrays. Simulations show that this particular optical device focuses the soft X‐ray radiation in a circular central spot with a radius of ∼4 µm. The study points out that such MCP‐based devices may achieve micrometre and sub‐micrometre spot sizes as required by many applications in the soft X‐ray range. Finally, based on experimental and theoretical results of the radiation transmission by this MCP‐based device, a new method to characterize the spatial properties of brilliant SR sources is discussed.